To the question of the identifying king Amazasp of Iberia, queen Dracontis and a royal official Anagranes mentioned in three Greek inscriptions found in Mtskheta - Phiphia, N.; Kobakhidze, K. (Материалы по археологии и истории античного и средневекового Причерноморья, 2022)
Three Greek inscriptions found in Mtskheta reveal interesting information about Ancient Iberian royal court. However, identification of each of the persons, especially the king, is quite problematic. Still, there are some possibilities to deal. King of Iberia is mentioned in all three inscriptions, one of them reveals his name fully, another one partially, while king’s name is lost in the third one, however, one passage may still give us some hints about his identity or at least about Roman aspirations of Iberian court. Queen Dracontis is known only from one inscription. As for the royal official — commander in-chief and the only minister of Iberian king Anagranes, he is mentioned in all three inscriptions, being himself the sponsor of all the constructions. The paper focuses more on the issue of identification of King Amazasp mentioned in these inscriptions and some other issues connected with the major topic.